Confocal reference free traction force microscopy - Martin Bergert (Nature Portfolio, 2016)
Traction force microscopy is an effective method of measuring forces between cells and their environment, but requires removing the cells to obtain a reference image. Here the authors use nanodrip printing of quantum dots into compliant substrates to provide a regular array of fiducial spots, removing the need for a reference image.